The magnificent lives of Marjorie Post : a novel - Pataki, Allison (Ballantine Books, 2022)
"An epic reimagining of the remarkable life of Marjorie Merriweather Post, the American heiress and trailblazing leader of the twentieth century, from the New York Times bestselling author of Sisi. Mrs. Post, the President and First Lady are here to see you. Such is Marjorie Merriweather Post's average evening. Presidents have come and gone, but she has hosted them all. Covered in diamonds and deemed American royalty, Marjorie nevertheless remains the product of her hardscrabble Midwestern roots and an insatiable drive to live, love, and give. A woman who has crawled through Moscow warehouses to rescue the Tsar's treasures, who has outrun the Nazis in London, and who has sat down to dinner with everyone from the homeless during the Great Depression to Kremlin leaders, from European royalty to Hollywood stars, Marjorie lived a grand life that defies imagination. Marjorie's was a journey that began on the Great Plains, where she glued cereal boxes in her father's barn as a young girl. None could have predicted that C. W. Post's homegrown Postum Cereal Company would fundamentally reshape the American way of life and grow into the vast General Foods empire, with Marjorie as its glittering heiress and leading lady. Not content to stay in her prescribed roles of coddled wife, mother, and hostess, Marjorie dared to demand more, making history as a leader in her family's business and a trailblazer in philanthropy and high society. Marjorie lived like an empress, worked like a titan of industry, and shaped a century. And yet Marjorie's story, though full of beauty and lived in her palatial homes like Mar-a-Lago, was equally marked by heartbreak. A wife four times over in vastly different, dramatic marriages, Marjorie sought her happily-ever-after with the blue-blooded playboy who could not outrun his demons, the charismatic financier whose charm could not conceal his betrayal, the diplomat with a dark side, and the bon vivant whose shocking secrets would shake their circles. Marjorie did everything on a grand scale, especially when it came to love"--